Arahan Pengendalian Alih Fungsi Lahan Kawasan Lindung Menjadi Kawasan Budidaya di Kelurahan Malino, Kecamatan Tinggimoncong, Kabupaten Gowa - Nur Hasanah; Rudi Latief; Rimba Arief (Journal of Urban Planning Studies, 2022)
This study aims to identify the factors causing the conversion of protected area land into cultivation areas and to identify directions for controlling the conversion of protected area land into cultivation areas in Malino Village, Tinggimoncong District, Gowa Regency. This study uses quantitative and qualitative methods with the data collection process through field observations, documentation and analysis documents where the sampling uses purposive sampling and simple random sampling. The data obtained were then analyzed using Chi-Square analysis and SWOT analysis. From the results of the analysis test carried out the factors causing the change in the function of the Protected Area land into Cultivation Areas in Malino Village, Tinggimoncong District, Gowa Regency, namely social factors marked by a lack of public understanding of the status of protected areas. So that the direction of control that is carried out is the strategy of implementing policies related to the status of protected areas to minimize the occurrence of land conversion in Malino Village, Tinggimoncong District, Gowa Regency.